Levitation force of Graphene added bulk MgB2 superconductor. (September 2021) - Tripathi, D.; Bhatnagar, Ashish; Raj, Shalini; Rai, D.K.; Dey, T.K.
Highlights: First report on vertical levitation force of Graphene added MgB2 . The experiment is performed in both zero field cooling and field cooling conditions. No hysteresis behaviour in levitation force was observed below 25 K. MgB2 added with 0.5 wt% Graphene display a significant enhancement in Levitation force in all the investigated temperature range. Abstract: The effect of Graphene addition on levitation/suspension force of bulk MgB2 superconductor has been studied in both zero field cooling (ZFC) and field cooling (FC) conditions at different temperatures. For this, the pristine, 0.5, 1 and 3 wt% of Graphene added bulk MgB2 samples are prepared by solid state reaction method under argon atmosphere. X-Ray diffraction (XRD) and scanning electron microscopy (SEM) of prepared samples have been performed for structural characterization and surface morphology respectively. The structural characterization shows well developed phase of MgB2 while hexagonal shaped grains are evident in SEM photographs. Electrical resistivity measured between 20 K and 300 K confirms a decrease in superconducting transition temperature (TC ) and increase in normal state resistivity of pristine MgB2 due to Graphene addition. The levitation force measurement under zero field cooling condition reveals that low level (0.5 wt%) of Graphene addition enhances the levitation force throughout the investigated temperature range. However the levitation force measurements performed at different initial field height under field cooling condition confirm the presence of both attractive and repulsive force. Further, the maximum levitation force (FMLF ) and maximum attractive force (FMAF ) estimated from the field cooling data of pure and Graphene added MgB2 is found to be a strong function of initial field cooling height (HFC ). The maximum repulsive/levitation force (FMLF ) increases exponentially with increase in initial field cooling height, while an exponential decrease in attractive force (FMAF ) of MgB2 has been observed with increase in initial field cooling height.